La punibilidad del sujeto masculino religioso hoy (2016)
Postmodernism as the conscience of the men of the century, brings a whole secular trend, which has led to a fragmentation of the subject and discourse that governs it. So legitimate self-through display, intercom, virtuality and speeches subjects emerge everywhere that. The male religious subject, and say has weakened and today the penalty, and configures network senses dangerous, which leads to increasing despair and disbelief; besides facilitating the strength of icons, without speech and subject they have taken place. The legal order sanctions, creates offenders subject to appease the collective imagination, that keep the status it once had devoted man. The alternative is to reconfigure and restore the role of religious, holy in terms of psychoanalysis.